The Effect of Working Posture on Musculoskeletal Disorders Complaints Moderated By Smoking Copra Workers in Tanjung Balai, Asahan Regency - Sheila Intan Mahendra; Isyatun Mardhiyah Syahri; Umi Salmah (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
Musculoskeletal complaints refer to discomfort or pain in the musculoskeletal system, ranging from mild to severe. One type of job that is particularly prone to musculoskeletal disorders is copra work, primarily due to poor working posture. This study aims to analyze the effect of working posture on musculoskeletal disorder complaints among copra workers in Tanjung Balai, Asahan Regency. The study is an analytical survey with a cross-sectional design, conducted in Bandar Jawa Village, Tanjung Balai Subdistrict, Asahan Regency, from December 2023 to February 2024. The study population consisted of all 139 copra workers in Bandar Jawa Village, and a sample of 104 workers was selected using the Slovin formula. The sampling technique employed was simple random sampling. Data were collected through surveys and questionnaires administered to respondents. The research instruments used were the Nordic Body Map and the Rapid Entire Body Assessment (REBA) evaluation sheet. Data analysis was performed using SPSS version 24, with three stages: univariate analysis using frequency, bivariate analysis using simple linear regression, and multivariate analysis using Moderated Regression Analysis (MRA) with a significance level of 95% (α=0.05). The results showed that working posture significantly affected musculoskeletal disorder complaints, moderated by smoking habits, with a p-value of 0.001. It can be concluded that smoking exacerbates the negative effects of poor working posture on musculoskeletal health, increasing the risk of injury and slowing recovery. It is recommended that copra workers take preventive measures against musculoskeletal disorder complaints by improving their work environment, paying attention to rest periods, engaging in light relaxation exercises, and that employers provide education on worker safety and health to copra workers. Keywords: Musculoskeletal disorders, Smoking, Work posture